Quality of quail eggs sold in São Luís, MA (Research, Society and Development, 2022)
I present work that assesses the quality of the eggs and the labels on the packaging of these products marketed in supermarkets in São Luís, MA. Foram analyzed 16 cards containing 720 quail eggs, coming from 12 supermarkets, being 6 varejistas and 6 attackers, besides, verifying the temperature and relative humidity of these establishments. As we showed forams validated regarding the integrity of the shell and carried out the microbiological analyzes regarding the contamination of mesophilic aerobic microorganisms, Escherichia coli and the investigation of Salmonella spp. The frequency of snatched eggs was high, occurring in 12.1% of the samples of varejistas and 11.6% of attackers. All samples were positive for mesophilic microorganisms, with average contaminations of 10² CFU/g in samples from both types of supermarkets. Contamination by Escherichia coli was found in 3 samples of eggs from grocery stores, with an average count of 5.50x10² NMP/g. To bacteria Salmonella spp. was not isolated in the analyzed samples. I did not agree with two labels regarding the information on the preparation and use of the products. All the samples are considered proper for consumption, according to current legislation. However, it is emphasized that there are economic losses for the consumer due to the discarding of lashed quail eggs and the need to improve hygienic conditions for eggs originating from attackist and varejista supermarkets.